STUDENTS’ GRAMMAR AND SENTENCE STRUCTURE OF THE TEXTS WRITTEN IN PARAGRAPH WRITING CLASS - Utari, Aisyah Ririn Perwikasih (Prominent, 2019)
Writing a text becomes the last skill in English learning. It needs a productive creativity and ability of the language used in it. The learners should listen, speak, read, and write to prove that they can use English well. Paragraph Writing is the first writing subject in the curriculum of English Education Department which should be taken by the students who are in the second semester. The activities of writing cover some processes in which they should know and apply the theories to practice writing some texts. Grammar and sentence structure are the crucial problems faced by the students. It needs an extra attention to make them understand about the components involved in this element of writing. The components are applied step by step from the beginning of the semester until it ends. The research problems are raised with some questions as follows: (1) what are the grammar and sentence structure’s components of the students’ text in Paragraph Writing class? ; (2) How is the analysis of grammar and sentence structure of the students’ text in Paragraph Writing class?. Further chapter of the research will provide the analyzed data and the result as the answer of the problems raised. The texts written by the students as the data source are randomly chosen from the whole final projects. From the result of the analysis, it can be found that 63% of the total texts are grammatically incorrect. The components of grammar structure are also recorded that there are 10% of the sentences are stringy, 5% comma splice, 10% run-on sentence, and 12% sentence fragment. Mostly, the problem that the students face are about concidering the tense and verb words. The conjunctions that influence the meaning are also mostly mis-used. The percentages found in the analysis show that most of the students make some errors in their grammar use in writing their paragraph writing project. The suggestions of the correct ones are also written in their text sheets to make further revisions. This can make them concern more to learn from the analysis. Paragraph writing class is like a stepping stone for them to start learning from mistakes.